USTEKINUMAB-INDUCED HYPOPHYSITIS IN CROHN’S DISEASE: A CASE REPORT - Sarvanandan, Tharsini; Chiew, Ken Seng; Vethakkan, Shireene; Ratnasingam, R. Jeyakantha; Lim, Lee-Ling; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Paramasivam, Sharmila (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Ustekinumab is a monoclonal antibody targeting IL-2 and IL-23 that has been used to treat psoriasis and more recently, inflammatory bowel disease. With the increased use of immunotherapy, immune-related adverse events are being reported more frequently. Ustekinumab has been reported to cause hypophysitis in a patient with psoriasis. CASE We report a case of a 29-year-old female with difficultto-treat Crohn’s disease since 2008. She has received azathioprine, methotrexate, infliximab, and adalimumab without favorable response. She subsequently underwent a right hemicolectomy and terminal ileal resection in 2017. She had previously been on prednisolone in 2012. She was started on ustekinumab in May 2020 and showed good clinical response. Twenty-seven months after starting ustekinumab, on routine investigation, she had a fasting blood glucose of 1.9 mmol/L. There were also some home capillary glucose readings of <3.5 mmol/L. She reported no signs of hypoglycemia and denied taking other medications or traditional supplements. She had been off all steroids for more than 10 years. She was clinically euthyroid with no history of polyuria or visual field defects. She had transient oligomenorrhea due to significant weight loss in 2020. Her BMI was 16.2. She had no signs of Cushing’s. Further workup revealed low cortisol level of 43 nmol/L with ACTH of 11 pg/ml. TFT was discordant with elevated FT4 of 34 pmol/L and normal TSH of 2.69 mIU/L, with no assay interference confirmed. Her prolactin level was normal at 374 mIU/L. Pituitary MRI showed loss of posterior pituitary bright spot, slightly thickened stalk with heterogeneity within the pituitary suggesting possible hypophysitis. She started hydrocortisone replacement and her hypoglycemia resolved. As she is currently responding well to the ustekinumab for her Crohn’s, she will be monitored periodically for progression of her hypophysitis. CONCLUSION Patients treated with ustekinumab should be monitored periodically for autoimmune endocrinopathies such as hypophysitis and thyroiditis.